Analisa Investasi Pengadaan Alat Support Tambang (Bulldozer D8R) Untuk Efisiensi Kinerja Bulldozer D10T Pt Cipta Kridatama Job Site PT. Adimitra Baratama Nusantara, Sanga-Sanga, Kutai Kartanegara. - Rijabul Mulia; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. During the excavation at the ABN site, PT CK was located in Kampung Jawa Village, Sanga-sanga District and Muara Kembang Village, Muara Jawa Subdistrict, Kutai Kartanegara District, East Kalimantan using a ripping unit with D10T bulldozer unit in breaking rocks. The purpose of ripping is to make the overburden material easier to dig by the loader and easy to haul by the conveyor. Looking at the open pit mining system where the Dozzer D10T is the main unit and is still used as a unit of support in achieving production targets, the authors "analyze investment procurement of mine support tools (Caterpillar D8R Bulldozer) for operational efficiency of Caterpillar D10T Bulldozer with IRR method" so that the D10T Dozzer unit designated as the main unit in production is not interrupted for support activities. Based on the results of observations in the field and data processing found D10T produces an IRR value of 75.47% by direct purchase, and 90.87% by leasing, at the value of NPV = 0. With the MARR value targeted by the company which is 16%, then investment this is declared feasible. Feasibility analysis for the D8R unit produces an IRR value of 154.83% by direct purchase, and 298.21% by leasing, at the value of NPV = 0. With the MARR value targeted by the company which is 16%, then the Invesatsi is declared feasible, and a leasing purchase system is highly recommended.Keywords:  IRR, Ripping, Bulldozer, Analyze Investment, Operational Efficiency.